2010
DOI: 10.1097/mbc.0b013e3283403537
|View full text |Cite
|
Sign up to set email alerts
|

Low vegetable intake is strongly associated with venous thromboembolism in Thai population

Abstract: Recent studies have demonstrated a much higher incidence of venous thromboembolism (VTE) among Asian patients compared with previous studies. This study aims to determine dietary and behavioral factors that may have contributed to this increase. A case-control study was conducted. Cases were objectively confirmed VTE between 2006 and 2009 at King Chulalongkorn Memorial Hospital. Patients with underlying cancer, antiphospholipid syndrome and arterial thrombosis were excluded. Controls were age and sex-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Worralurt and Taneepanichskul published a small casecontrol study including 70 women aged 15-49 years who were diagnosed with VTE in King Chulalongkorn Memorial Hospital (Thailand) between the years 1995 and 2004 (mean age 37 ± 4 years), as well as 140 healthy female patients who attended the gynecological clinic for annual check up during the same period (mean age 36 ± 10 years) [27]. There is no significant difference in the VTE risk between subjects reporting any type of alcohol consumption and in those reporting no intake (OR 0.9, 95 % CI 0.47-1.65).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Worralurt and Taneepanichskul published a small casecontrol study including 70 women aged 15-49 years who were diagnosed with VTE in King Chulalongkorn Memorial Hospital (Thailand) between the years 1995 and 2004 (mean age 37 ± 4 years), as well as 140 healthy female patients who attended the gynecological clinic for annual check up during the same period (mean age 36 ± 10 years) [27]. There is no significant difference in the VTE risk between subjects reporting any type of alcohol consumption and in those reporting no intake (OR 0.9, 95 % CI 0.47-1.65).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Lifestyle factors such as diet and physical activity may also influence the relation between obesity and venous thrombosis. However, most, but not all, 86,87 studies have reported only a weak 88 or no association [89][90][91] between diet and venous thrombosis, also within obese subjects. 89 Current evidence on physical activity and venous thrombosis is not consistent.…”
Section: Other Factors That May Affect the Relation Between Obesity Amentioning
confidence: 99%
“…Due to the outcome of an earlier study published by Steffen et al in 2007 [16], a large consensus has been reached that lower consumption of red and processed meat would be advisable for reducing the risk of VTE, a notion that was also officially endorsed by some recommendations [7,25]. Additional studies were then published, which have partially or completely contradicted this previous evidence [17][18][19][20][21][22]. Unlike CVD and colorectal cancer, the results of this critical review of the current scientific literature shows that whether or not a pathophysiological link may exist between venous thrombosis and red or processed meat consumption, this should be definitely weak at best.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, one major limitation for analyzing data available in the current scientific literature is represented by the heterogeneity of the definitions of "meat" used across different studies, which makes it impossible the use of a meta-analytic approach for pooling data. More specifically, no clear indication was provided on the types of meat included under the category of "red and processed meat" in the vast majority of studies reviewed in this article [16][17][18][19][20][21], whereas one study only included moderate to high fat meat products and dairy products in the component "meat" [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation